Readiness of health facilities to deliver safe male circumcision services in Tanzania: a descriptive study - Frank Felix Mosha; Mwita Wambura; Joseph R. Mwanga; Jacklin F. Mosha; Gerry Mshana; John Changalucha (PAGEPress Publications, 2013)
Assessing the readiness of health facilities to deliver safe male circumcision services is more important in sub-Saharan Africa because of the inadequacy state of health facilities in many ways. The World Health Organization recommends that only facilities equipped with available trained staff, capable to perform at least minor surgery, able to offer minimum MC package and appropriate equipment for resuscitation, and compliant with requirements for sterilization and infection control should be allowed to deliver safe circumcision services. A cross-sectional study using quantitative data collection technique was conducted to assess the readiness of the health facilities to deliver safe circumcision services in selected districts of Tanzania. All hospitals, health centres and 30% of all dispensaries in these districts were selected to participate in the study. Face-toface questionnaires were administered to the heads of the health facilities and to health practitioners. Overall, 49/69 (59%) of the facilities visited provided circumcision services and only 46/203 (24%) of the health practitioners performed circumcision procedures. These were mainly assistant medical officers and clinical officers. The vast majority – 190/203 (95%) – of the health practitioners require additional training prior to providing circumcision services. Most facilities – 63/69 (91%) – had all basic supplies (gloves, basin, chlorine and waste disposal) necessary for infection prevention, 44/69 (65%) provided condoms, HIV counselling and testing, and sexuallytransmitted infections services, while 62/69 (90%) had the capability to perform at least minor surgery. However, only 25/69 (36%) and 15/69 (22%) of the facilities had functioning sterilization equipment and appropriate resuscitation equipment, respectively. There is readiness for roll out of circumcision services; however, more practitioners need to be trained on circumcision procedures, demand forecasting. Sterilization equipment for infection prevention and resuscitation equipment should also be made available.